Retracting ball onto sphere in $BC_0(\mathbb R)$ - Piasecki, Łukasz (Topological Methods in Nonlinear Analysis, 2009)
In infinite dimensional Banach spaces the unit sphere is a lipschitzian retract of the unit ball. We use the space of continuous functions vanishing at a point to provide an example of such retraction having relatively small Lipschitz constant.